The green glass sea - Klages, Ellen, 1954- (New York, N.Y. : Viking, 2006)
It is 1943, and 11-year-old Dewey Kerrigan is traveling west on a train to live with her scientist father--but no one will tell her exactly where he is. When she reaches Los Alamos, New Mexico, she learns why: he's working on a top secret government program.
A Junior Library Guild selection.
Keywords: Fathers and daughters -- Juvenile fiction; Scientists -- Juvenile fiction; Friendship -- Juvenile fiction; Fathers and daughters -- Fiction; Scientists -- Fiction; Friendship -- Fiction